Principles of water quality control - Tebbutt, T. H. Y. (Pergamon international library of science, technology, engineering, and social studies., 1983)
This popular and widely used text has been thoroughly revised and expanded to include new chapters which reflect the growth in awareness of the problems of environmental pollution, the importance of environmental protection, and the vital role of water in the developing countries. Also covers the basic characteristics of waters and wastewaters, relevant aspects of microbiology, water pollution and the theoretical and practical basis of treatment processes. Includes numerous problems with answers. A useful list of further reading has been expanded (200 literature references approximately) to.